Pitfalls in Neuroimaging of Headache: A Case Report and Review of the Literature. (28th February 2013) - Vallamkondu, V.; Shakeel, M.; Hussain, A.; McAteer, D.
Abstract : Headache is a common symptom, with a lifetime prevalence of over 90% of the general population in the United Kingdom (UK). It accounts for 4.4% of consultations in primary care and 30% of neurology outpatient consultations. Neuroimaging is indicated in patients with red flag features for secondary headaches. The guidelines recommend CT or MRI scan to identify any intracranial pathology. We present a unique case where the initial noncontrast CT scan failed to identify a potential treatable cause for headache. A middle aged man presented with headache and underwent a CT scan without contrast enhancement. The scan was reported as normal. The headache persisted for years and the patient underwent a staging CT scan to investigate an oropharyngeal cancer. This repeat CT scan utilized contrast enhancement and revealed a meningioma. Along with other symptoms, headache is an established presenting complaint in patients with meningioma. The contrast enhanced CT brain proved superior to a nonenhanced CT scan in identifying the meningioma. In a patient with persistent headache where other causes are excluded and a scan is to be requested, perhaps contrast enhanced CT is a better option than a plain CT scan of brain.